A functional near-infrared spectroscopy study of the effects of configural properties on sustained attention - de Joux, Neil; Wilson, Kyle M.; Russell, Paul N.; Finkbeiner, Kristen M.; Helton, William S. (Elsevier, 2017)
Forty-five participants performed a vigilance task during which they were required to respond to a critical signal at a local feature level, while the global display was altered between groups (either a circle, a circle broken apart and reversed, or a reconnected figure). The shape in two of the groups formed a configurative whole (the circle and reconnected conditions), while the remaining shape had no complete global element (broken circle). Performance matched the results found in the previous experiments using this stimulus set, where a configural superiority effect was found to influence accuracy over time. Physiological data, measured using functional near-infrared spectroscopy, revealed elevated activation in the right pre-frontal cortex compared to the left pre-frontal cortex during the task. Additionally, bilateral activation was found in the conditions that formed configurative wholes, while hemispheric differences over time were found in the condition that did not. These findings suggest that configural aspects of stimuli may explain why non-typical laterality effects have been found in similar research.